Human toxocariosis: Seroprevalence in Lima inhabitans by ELISA technique - Espinoza, Yrma (2003)
Objective: To estimate seroprevalence of human toxocariosis in Lima inhabitants. Design: Cross-sectional study, non aleatory selection. Material and methods: To people living in Lima city urban marginal communities, an interview and clinical examination were done and serum samples obtained to detect antibodies against Toxocara by ELISA technique. Stool samples were also obtained to check parasites causing cross reactions with serology. Results: From 553 persons examined 23,3% were reactive. There were no sex differences and ELISA results related to anemia, leucocytosis, eosinophilia or intestinal parasites. People older than 15 yearold had twice the possibility to be reactive. Most frequent symptom in positive individuals was decrease of visual capacity. Most frequent parasites were Blastocystis hominis, Entamoeba coli, Giardia lamblia. Conclusions: Human toxocariosis is frequent in Lima inhabitants. There is no statistical association between anemia and changes in leucocyte formula with ELISA result. It is necessary to develop diffusion programs for early infection detection and prevention.